(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2025)
The Observatory of Critical Editions (OEC) has developed a database to collect, organise and consult files and reviews on critical editions of ancient, medieval, modern and contemporary texts. The article explores the functioning, purpose and methodological implications of this tool, with particular attention to the disciplinary transversality it promotes. Through concrete examples, the contribution of the OEC to the reflection on editorial practices and to the sharing of experiences between different philologies is highlighted.